Thermal requirements for development of aphidophagous Coccinellidae (Coleoptera), Chrysopidae, Hemerobiidae (Neuroptera), and Syrphidae (Diptera): some general trends - Honěk, A; Kocourek, F (Oecologia, 1988)
The sum of effective temperatures (SET) and lower development threshold (LDT) were established for eggs and/or pupae of central European populations of 20 species of chrysopid, coccinellid, hemerobiid, and syrphid predators of aphids. LDT ranged between 5.6° and 12.2°C, SET between 38.3 and 140.9 day degrees (dd), with broad overlap among stages and taxa. When LDT was plotted against SET, the data for both eggs and pupae were scattered along a single regression line which predicted a 0.47°C decrease in LDT per 10 dd increase in SET (r=-0.77, p<0.001). A regression calculated from published data from all over the world predicted a 0.24°C/10 dd decrease in LDT, and the data were more scattered (r=-0.38, p<0.01). This is perhaps the first report on the functional relationship between LDT and SET at the interspecific level. The species and stages differed in typical development length (VDL) and in the extent of its deceleration by low temperatures (DD). DD increased with increasing VDL, but the relative effect of low temperature on development length (DD/VDL ratio) reflected thermal adaptations consistent with the life history of the species. Polyvoltine species were less affected by low temperatures than monovoltine species, particularly the thermophilic ones.
Keywords: Life history; Voltinism; Sum of effective temperatures; Temperature; Lower development threshold